Perlindungan Hukum Bagi Konsumen Dalam Penggunaan E-Wallet DANA Terhadap Transaksi Digital - Aurelita, Mira; Bilqis, Audrey Azka; Sahara, Melian; Suhanda, Ariq Naufal Attalah; Gunawan, Rafy Akmal; Sakti, Muthia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Technological developments in the economic sector not only provide convenience in transactions, but also have challenges in implementation. Challenges related to security and consumer protection in digital transactions. The aim of this research is to find out the legal regulations for consumer protection for digital transactions in the era of digitalization and to find out legal protection for consumers in the DANA digital transaction application. The type of research method used in this research is a normative juridical approach. In this case, the data sources relied on are secondary data, such as statutory regulations, scientific journals and legal literature. The data collection method uses library research, and data analysis is carried out using a qualitative approach. The results of this research are that to protect consumers, the ITE Law and UUPK have provided a clear legal umbrella. Article 7 letter (f) UUPK regulates the responsibilities of e-wallet parties, including providing compensation if there is a violation of the agreement. Meanwhile, Article 19 explains the provisions for compensation for losses that may arise from the use of e-wallet services, confirming the responsibility of service providers towards their consumers. Thus, clear and firm legal protection for consumers in electronic transactions is very important to prevent losses in the future, as well as liability for service providers.